Penerapan Sanksi Pidana terhadap Kejahatan Siber: Sebuah Kajian terhadap Perkembangan Hukum - Syahriati Fakhriah; Inayatul Mutmainnah (PT. Banjarese Pacific Indonesia, 2024)
Cybercrime has become a serious challenge in the digital age, requiring a dynamic legal approach to respond to this threat. This study aims to investigate legal developments in the application of criminal sanctions against cybercrimes. Through a critical analysis of various cases and regulatory developments, this study will explore the effectiveness of criminal sanctions applied in tackling cybercrime. This research method includes comparative law analysis, case studies, and interviews with criminal law experts. Research findings will include the evolution of the concept of cybercrime, the legal challenges faced in enforcing criminal sanctions, and the impact of the application of criminal law on cybersecurity levels The results of this study are expected to provide in-depth insight into the progress of criminal law in responding to cybercrime, as well as provide a basis for further improvement and development in the relevant legal framework. The practical implications of this research are expected to help authorities, legal professionals, and academics in understanding the dynamics of criminal law related to cybercrime, so as to formulate policies that are more effective and responsive to evolving cybersecurity threats.